New governance regulation and lawyers: When substantive compliance erodes legal professionalism. Issue 3 (24th October 2018) - Aulakh, Sundeep; Kirkpatrick, Ian
ABSTRACT: A dominant theme within institutional theory is that organizational responses to regulatory demands will be characterized by decoupling. However, this assumption rests on regulation as a coercive force. The emergence of 'new governance regulation' and the freedom afforded to firms to tailor regulatory demands to local circumstances should, theoretically, foster greater commitment to, achievement of, regulatory goals. Focusing on the responses of solicitor practices in England and Wales to outcome-focused regulation, this paper explores the extent to which the flexibility of NGR triggers substantive compliance. Drawing on multiple data sources, we find that law firms made significant investments in compliance infrastructures and developed strategies to integrate compliance into work structures and day to day activities. Whilst their responses indicate substantive compliance, core regulatory goals were only partially met.